2009
DOI: 10.2478/s11687-009-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two compost soil amendments, based on municipal green and penicillin production wastes, on plant parasitic nematodes

Abstract: SummarySuppressive effect of two composts, applied at five doses (0 %, 1 %, 2.5 %, 5 % and 10 % w/w), was studied on spring barley to control different genera of plant parasitic nematodes in potting mixtures. Amendment of soil with these materials resulted in a significant decreasing effect of plant parasitic nematode populations. The best reduction of number of plant parasitic nematodes was found for the nematode genera Bitylenchus, Helicotylenchus, Heterodera, Paratylenchus and Rotylenchulus by a municipal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Moreover, most composts tested in this experiment were recently found also suppressive on the cyst nematode Globodera rostochiensis Woll. on potato and on seven different plant-parasitic nematode genera in natural grassland soil (Renčo et al, 2007(Renčo et al, , 2009. Previous findings on RKN suppression by compost amendments were quite contrasting, as several authors documented a satisfactory nematode control but inconsistent results were also reported (Akhtar & Malik, 2000).…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…Moreover, most composts tested in this experiment were recently found also suppressive on the cyst nematode Globodera rostochiensis Woll. on potato and on seven different plant-parasitic nematode genera in natural grassland soil (Renčo et al, 2007(Renčo et al, , 2009. Previous findings on RKN suppression by compost amendments were quite contrasting, as several authors documented a satisfactory nematode control but inconsistent results were also reported (Akhtar & Malik, 2000).…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…The changes in C:N ratio can influence the plant parasitic nematodes. The higher C:N ratio may be connected with a higher level of defensive compounds in plant tissues (Hartley et al, 1995), which might deter plant-feeding nematodes (Mattson, 1980;Renčo et al, 2009Renčo et al, , 2010b. Due to the regular application of manure and fertilizers in the investigated hop gardens, the low C:N ratio, good availability of N and P, and rich root system can be expected and those can explain high abundances of "large" plant parasitic nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Akhtar and Mahmood (1996) found a significant reduction of plant parasite and increase of predatory and free-living nematodes after application of all tested materials after an application of different rates of oilcakes of neem (Azadirachta indica) and castor (Ricinus commnunis), composted manure and urea, as well as using of composted manure combined with Tagetes erecta Renčo et al, 2009 7 (Akhtar, 1998). Dmowska and Kozlowska (1988) recorded the increase in bacteriovorous nematodes after using a pig and cattle manure, especially Rhabditida -saprobionts.…”
Section: The Organic Amendments Effect On Nematode Community Changesmentioning
confidence: 99%
“…Many organic material wastes represent an important resource of nitrogen, phosphorous, calcium and other elements as zinc, copper, magnesium essential to plant growth (Tester, 1990). There are sufficient data to indicate that organic materials have positive effect on soil structure, improve plant growth and yields and reduce disease impact caused by a wide range of plant pests including bacteria, soil-borne pathogens and phytoparasitic nematodes species (Akhtar & Mahmood, 1996;D'Addabbo & Sasanelli 1996aAbawi & Widmer, 2000;Renčo et al 2007Renčo et al , 2009Renčo et al , 2010Atungwu, 2012). In particular, the suppressive effect of soil amendments, with a wide range of composted waste materials, on plant parasitic nematodes was largely and frequently docu-mented, although an inconsistent nematode control or variable effects were also described in literature (Szczech et al, 1993;McSorley & Gallagher, 1995;Akhtar & Malik, 2000).…”
Section: Introductionmentioning
confidence: 99%